Dufour and Soret effects on MHD free convective heat and mass transfer flow past a vertical porous flat plate embedded in a porous medium - Alam, Md Shariful; Rahman, Mohammad Mansur (Journal of Naval Architecture and Marine Engineering, 2009)
A two-dimensional steady MHD free convection and mass transfer flow past a semi-infinite vertical porous plate in a porous medium has been studied numerically including the Dufour and Soret effects. The resulting momentum, energy and concentration equations are then made similar by introducing the usual similarity transformations. These similar equations are then solved numerically by using the Nachtsheim-Swigert shooting method along with Runge-Kutta sixth order integration scheme. The numerical results are displayed graphically showing the effects of various parameters entering into the problem. Finally, the local values of the skin-friction coefficient (Cf), Nusselt number (Nu) and Sherwood number (Sh) are also shown in tabular form. Keywords: MHD, Free convection, Vertical plate, Steady flow, Porous medium, Dufour effect, Soret effect. doi: 10.3329/jname.v2i1.2030 Journal of Naval Architecture and Marine Engineering 2(1)(2005) 55-65